The impact of minimum wage changes on management in the Czech Republic - Natalie Uhrová; Petr Skalka (DANUBE: Law, Economics and Social Issues Review, 2016)
The extent of social security contributions paid by both employers and employees in the Czech Republic is considered one of the biggest problems of the Czech economy. At the same time, the minimum wage in the Czech Republic has been repeatedly changed in recent years and even months, and thus the aim of this paper is to identify and discuss possible consequent changes in managerial decisions in Czech firms that could be examined in further analyses. We suggest the hypothesis that Czech firms are lowering their costs via the substitution of employment agreements for employment contracts in order to avoid social security contributions paid by the employer.
Keywords: 330; Social Security Contribution; Minimum Wage; Employment Agreement